2021
DOI: 10.3389/fimmu.2021.718432
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Mononuclear Phagocytes in Healthy Arteries and Atherosclerosis

Abstract: Monocytes and macrophages play essential roles in all stages of atherosclerosis – from early precursor lesions to advanced stages of the disease. Intima-resident macrophages are among the first cells to be confronted with the influx and retention of apolipoprotein B-containing lipoproteins at the onset of hypercholesterolemia and atherosclerosis development. In this review, we outline the trafficking of monocytes and macrophages in and out of the healthy aorta, as well as the adaptation of their migratory beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 222 publications
(406 reference statements)
0
2
0
Order By: Relevance
“…An essential stage in the inflammatory process involves the penetration of monocytes into the subendothelial region of major arteries and their subsequent transformation into tissue macrophages. The activation and functioning of these macrophages are regulated by the cytokines present in the inflammatory environment of the atherosclerotic lesion [194]. MASLD exhibits a strong correlation with AS and appears to serve as an early risk factor for the development of AS [195].…”
Section: Adiponectinmentioning
confidence: 99%
“…An essential stage in the inflammatory process involves the penetration of monocytes into the subendothelial region of major arteries and their subsequent transformation into tissue macrophages. The activation and functioning of these macrophages are regulated by the cytokines present in the inflammatory environment of the atherosclerotic lesion [194]. MASLD exhibits a strong correlation with AS and appears to serve as an early risk factor for the development of AS [195].…”
Section: Adiponectinmentioning
confidence: 99%
“…359 Cytokines released by mononuclear cells stimulate the proliferation of smooth muscle cells in the media of blood vessels and the new intima. 360 In addition, mononuclear cells activate into macrophages, during which smooth muscle cells of the new intima ingest lipids to become foam cells, forming atheromatous plaques. 361,362 Atherogenesis is related to hypoxia.…”
Section: Hypoxia In Atherosclerosismentioning
confidence: 99%
“…Also, the underlying mechanism of macrophages and foam cells involved in atherosclerotic plaque instability and rupture has been partially characterized [15,16]. Numerous studies have reported that monocytes play an essential role in atherosclerotic, but monocyteassociated genes' effect on plaque instability is still not very clear [17][18][19][20][21]. Therefore, it is essential to explore the clinical significance and potential mechanisms of monocyte-associated genes in atherosclerotic plaque instability through the combined single-cell sequencing and transcriptomics data analysis.…”
Section: Introductionmentioning
confidence: 99%